Rekonstruksi Tujuan Pemidanaan dalam Pemberantasan Tindak Pidana Korupsi - Slamet Haryadi (PRANATA HUKUM, 2012)
Problem of Crime since long time until now represent problem which is aktual and become diskursus which no desisting in crime hokum. Related of eradication of corruption doing an injustice of is problem of crime by judge become public focus, with many crime decision him which do not express sense of justice. Reconstruct crime to perpetrator of important corruption doing an injustice in order to harmonizing the target of crime and penjaatuhan of crime. First, placing judge moral as assessment corridor and base of determination of guilty law do not it him defendant pursuant to real correct consideration. Both, Formulating again the target of crime at prevention of corruption doing an injustice, Pemasyarakatan punished, solving of conflict generated by by doing an injustice, curing balance, and deliver to feel peace in society. Crime do not be meant to suffer and do not be allowed to condescend human being.